IMPLEMENTATION OF ALTERNATIVE DISPUTE RESOLUTION IN RESOLUTION OF DISPUTES DUE TO BUILDING FAILURE IN BUILDING CONTRACTING AGREEMENTS - Muhammad Ari Syahputra; Redyanto Sidi; Henry Aspan (RADJA PUBLIKA, 2023)
There is a building failure in terms of the time period after the construction work was handed over for the last time (FHO), when viewed from the substance of the work, the building failure has occurred in part or in full malfunction of the results of the construction work from a technical, benefit, safety and health perspective Work; in summary the time after the FHO, due to non-functioning construction work results. The specifications of the research used are descriptive analysis and normative legal research. The technique of collecting legal material that will be used as a source in this study is library research, namely collecting legal material by reading laws and regulations, official documents, journals, articles from the internet, as well as other literature that is closely related to The issues discussed are based on secondary legal materials. The implementation of the project or building construction involves various parties who take part in it, namely the employer, the architect and the contractor. A contracting agreement is an agreement between one party (the contractor) and another party or (the contractor) in which he binds himself to carry out a work regarding the manufacture of a work (het maken van werk) by receiving a price according to the specified price. Efforts to settle alternative dispute resolution in the settlement of contracting disputes through several efforts such as arbitration, negotiation, mediation or by making efforts or applying court channels if they are not resolved out of court.